Genomic Profiling Identified ERCC2 E606Q Mutation in Helicase Domain Respond to Platinum-Based Neoadjuvant Therapy in Urothelial Bladder Cancer - Hirotsu, Yosuke; Yokoyama, Hitoshi; Amemiya, Kenji; Hagimoto, Takashi; Hosaka, Kyoko; Oyama, Toshio; Mochizuki, Hitoshi; Omata, Masao (Frontiers in Oncology, 2020)
Genomic profiling of tumours enables therapeutic decisions, and identifying drug-matched mutations will prolong survival and prognosis. Here, we generated a custom panel for detecting genetic alterations in 19 patients with urothelial bladder cancer. This panel targeted 71 genes associated with urological cancer. Targeted sequencing was performed on formalin-fixed paraffin-embedded tumour tissues. Paired patient-matched tumour and blood samples were subjected to this analysis. A total of 142 somatic mutations were detected in 19 tumour tissues. At least one nonsynonymous mutation was detected in all tumour tissues, and KDM6A, KMT2D, TP53, KMT2C, PIK3CA, and ERCC2 were recurrently mutated. Chromatin remodelling and epigenetic modifier genes are frequently mutated. Of 142 mutations, 69 mutations (49%) were annotated to have oncogenic potential. Furthermore, 74% of patients were expected to receive targeted therapy due to drug-matched mutations being identified in their tumours. Among this cohort, a patient harboured an ERCC2 helicase domain mutation and would be expected to respond to platinum-based therapy. As expected, the patient received carboplatin-containing neoadjuvant therapy with a remarkable response. Furthermore, tumour-derived mutations in urine were rapidly decreased after neoadjuvant therapy. These results suggested targeted sequencing could help to detect drug-matched somatic mutations and indicate single or combination therapy for cancer patients.